Pelatihan Pendamping Korban Kekerasan Seksual di Maluku Tengah - Prisca Diantra Sampe; Neleke Huliselan; Caroline Alexandra Seipala (Arfah BHMS Foundation, 2026)
Violence cases are currently rampant in the community, therefore appropriate handling is required. Training on violence counselors is needed to address the community's needs regarding handling violence cases, so that the TIM can help address problems or issues of violence in Central Maluku. This training has seen drastic changes, as the TIM is able to understand how to report cases, assist victims, provide trauma recovery, and coordinate with institutions. With this knowledge, victims will be more confident in reporting cases due to the sense of security and support from the counselor team. Victims will receive integrated psychological, legal, and social services, which will help them recover emotionally and socially. Cross-sectoral collaboration will expedite the handling and decision-making process. Thus, the TIM can assist and build collaboration with the government.